2021
DOI: 10.1007/s12182-020-00539-6
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective optimization and experiment of nylon cord rubber in expandable packer

Abstract: Nylon cord rubber has the advantages of small residual deformation and is easy to lift and lower the tubing string in low-permeability oil and gas reservoirs. However, it is associated with low-pressure resistance and poor sealing performance. To enhance the performance of nylon cord rubber, a three-dimensional numerical model of the nylon cord rubber was established and its accuracy experimentally determined. The Plackett–Burman test, the Steepest climbing test and the Response surface method were used to acq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…As the main sealing element of the annular packer, the sealing performance of the rubber cylinder directly determines the setting effect of the downhole packer, especially in high-temperature and high-pressure environments [10]. Zhang et al used a genetic algorithm to determine the optimal structural parameters of nylon cord rubber according to the field operation, which improved the sealing performance of the rubber cylinder [11]. Hu optimized the structural parameters of the rubber cylinder of the compression packer by analyzing the failure mechanism and provided a better selection of rubber materials [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…As the main sealing element of the annular packer, the sealing performance of the rubber cylinder directly determines the setting effect of the downhole packer, especially in high-temperature and high-pressure environments [10]. Zhang et al used a genetic algorithm to determine the optimal structural parameters of nylon cord rubber according to the field operation, which improved the sealing performance of the rubber cylinder [11]. Hu optimized the structural parameters of the rubber cylinder of the compression packer by analyzing the failure mechanism and provided a better selection of rubber materials [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [9] found that the trapezoidal groove was the most proper shape for packer rubber, and the sealing property could be better when the bearing flow ring was installed inside the trapezoidal groove. Zhang et al [10] determined the best structural Energies 2022, 15, 7962 2 of 10 parameters of nylon cord rubber, which increased the load-bearing capacity of the packer by 25% and the sealing performance by 66%. Dong et al [11] proposed a high-pressure sealing anti-shoulder (HPS-PSP) packer, which effectively solved the problems of hose shoulder protrusion and insufficient sealing performance.…”
Section: Introductionmentioning
confidence: 99%